Optimizing Educational Facilities to Improve the Quality of Learning at the Daarul Ishlah Assyafi'iyah Islamic Boarding School - Hilal Solikin; Desi Fitriyani; Martina Zulpiani; Febi Oktaviani; Putri Husnul Amanatus sholeha; Amalia Maimunah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the availability of educational facilities and their role in improving the quality of teaching and learning at the Daarul Ishlah Assyafi'iyah Islamic Boarding School in Sungai Loban District, Tanah Bumbu Regency. This study uses a qualitative approach with a descriptive type. Data collection techniques were carried out through observation, interviews, and documentation of 9 informants selected by purposive sampling. The results of the study indicate that the Daarul Ishlah Assyafi'iyah Islamic Boarding School has provided 13 types of educational facilities, including classrooms, dormitories, UKS, OSDIA rooms, mosques/prayer rooms, toilets, bathrooms, computer laboratories, teachers' rooms, cottage kitchens, canteens, communal dining areas, and fields. In general, the facilities are in good condition, although there are still some limitations, such as the lack of fans in classrooms, the less than optimal function of the UKS, and the existence of damaged bathrooms. Educational facilities play a crucial role in improving the quality of learning, as identified in five dimensions: as enablers of the learning process, as vehicles for character development in students, as motivators for learning, as supporters of innovative learning methods, and as supporters of the holistic development of students. Therefore, optimizing educational facilities through effective and sustainable management is a crucial factor in improving the quality of teaching and learning in Islamic boarding schools.